OP0154 A NOVEL RELA TRUNCATION IN A 3-GENERATION FAMILY WITH BEHCET'S DISEASE ALTERS THE APOPTOTIC RESPONSE TO INFLAMMATORY STIMULANTS. (June 2019) - Dorris, Emma; Adeeb, Fahd; Lawless, Dylan; Ng, Wan Lin; Anjum, Aqeel; Morgan, Niamh; Cummins, Eoin; Savic, Sinisa; Fraser, Alexander; Wilson, Gerry
Abstract : Background: Bechet's disease (BD) is a heterogeneous multifactorial auto-inflammatory condition characterised by recurrent episodes of oral and genital ulceration, uveitis and skin lesions, with less frequent involvement of the gastrointestinal tract, large blood vessels and central nervous system. The NF-κB pathway is a 'master-regulator' of immune and inflammatory signaling, with the ability to control the expression of key inflammatory genes and genes associated with apoptosis and proliferation. Objectives: To identify the pathobiology associated with a novel genetic mutation identified in a 3-generation family with Behçet's-like mucocutaneous ulceration syndrome, primarily involving childhood-onset chronic oral and genital ulcers. Methods: The novel RELA mutation was identified using whole exome sequencing. Immunoblot of peripheral blood mononuclear cell (PBMCs) lysates from affected family members was used to determine if the predicted truncated protein was expressed. PBMCs were stimulated with TNF; NFkB phosphorylation was measured relative to unstimulated cells form affected and unaffected family members. HEK293T cells transfected with plasmids encoding either wild-type or the novel RELA-mutant and overexpression confirmed via immunoblot. An in vitro model of the RELA truncation was used to observe the effect of the RELA truncation on response to TNF stimulation. Apoptosis protein arrays, western blots, and ELISA assays were used to investigate the effect of TNF on wild-type RELA compared to the mutant protein. Mouse Embryonic Fibroblasts (MEFs) isolated from RELA -/- mice, which do not express endogenous RELA, were transfected with plasmids encoding either wild-type or the novel RELA-mutant. Wild Type MEF cells (with endogenous RELA) were used as a control. Cells were stimulated with LPS (2.5ug/ml) or no treatment control for 12 hours. Results: A heterozygous cysteine deletion at position 1459 in RELA was detected in all affected individuals as previously reported. This mutation results in a frameshift His487ThrfsTer7, producing a truncated protein of 492 amino acids. RELAHis487ThrfsTer7 heterozygotes have different phosphorylation kinetics of key NFkB pathway proteins in response to TNF compared to wild-type controls. Cells overexpressing RELAHis487ThrfsTer7, had increased pro-apoptotic proteins (BAD, cleaved caspase 3 and SMAC) whereas anti-apoptotic proteins (BCL2, CLASPIN) were decreased compared to cells transfected with wildtype RELA. Cells transfected with RELAHis487ThrfsTer7 were less sensitive to TNF stimulation compared to wild-type controls, as measured by induction of TNF-sensitive proteins. Conclusion: This study gives novel information on both the genetic basis and biological mechanisms of BD in individual families. Familial mutations that induce haploinsufficiency of RELA have recently been associated with BD. However, the His487ThrfsTer7 results in protein truncation rather than haploinsufficiency. Our study supports several recently published studies that loss-of-function mutations in the NF-κB pathway are linked with the development of familial early-onset BD-like syndromes. We propose that RELAHis487ThrfsTer7 causes altered NFκB signaling resulting in reduced mucosal cell recovery and the observed Behçet's-like mucocutaneous ulceration syndrome. Disclosure of Interests: : Emma Dorris: None declared, fahd adeeb: None declared, Dylan Lawless: None declared, Wan Lin Ng: None declared, Aqeel Anjum: None declared, Niamh Morgan: None declared, Eoin Cummins: None declared, Sinisa Savic Grant/research support from: Novartis and Sobi, Alexander Fraser: None declared, Gerry Wilson: None declared